2013
DOI: 10.1161/hypertensionaha.113.01425
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Hypoxia, Attributable to Increased Oxygen Consumption, Induces Nephropathy Independently of Hyperglycemia and Oxidative Stress

Abstract: Diabetic nephropathy is strongly associated with both increased oxidative stress and kidney tissue hypoxia. The increased oxidative stress causes increased kidney oxygen consumption resulting in kidney tissue hypoxia. It has so far been difficult to determine the role of kidney hypoxia per se for the development of nephropathy. We tested the hypothesis that kidney hypoxia, without confounding factors such as hyperglycemia or elevated oxidative stress, results in nephropathy. To induce kidney hypoxia, dinitroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 56 publications
4
127
3
1
Order By: Relevance
“…We demonstrated that TR CTLs boosted by PD-L1 mAb carry activated mitochondria with higher ROS production, and found that administration of ROS generators as well as uncouplers has synergistic effects with PD-1 blockade on tumor-growth inhibition. The uncouplers' synergistic effect may be due to their ability to induce cellular ROS through hypoxia or feedback mitochondrial proliferation, as a ROS scavenger cancelled the synergistic effect of uncouplers and CTLs stimulated with uncouplers contained higher ROS (34,35). We found that the administration of the uncouplers alone did not show a direct impact on the growth or gene expression of tumor cells.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We demonstrated that TR CTLs boosted by PD-L1 mAb carry activated mitochondria with higher ROS production, and found that administration of ROS generators as well as uncouplers has synergistic effects with PD-1 blockade on tumor-growth inhibition. The uncouplers' synergistic effect may be due to their ability to induce cellular ROS through hypoxia or feedback mitochondrial proliferation, as a ROS scavenger cancelled the synergistic effect of uncouplers and CTLs stimulated with uncouplers contained higher ROS (34,35). We found that the administration of the uncouplers alone did not show a direct impact on the growth or gene expression of tumor cells.…”
Section: Discussionmentioning
confidence: 72%
“…Although chemical uncouplers are known to decrease ROS production in isolated mitochondria (30,31), there are reports that the uncouplers rather increase mitochondrial ROS production in cells through hypoxia and HIF-1α activity (32)(33)(34). We thus tested the effect of carbonylcyanide-p-trifluoromethoxyphenylhydrazone (FCCP) and 2,4-dinitrophenol (DNP), and compared with oligomycin (an ATP synthase inhibitor) as control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[261][262][263][264][265] Therefore, by inducing pro-inflammatory adhesion molecules and chemokines, hypoxia causes the accumulation of macrophages in the kidney that produce profibrotic cytokines such as transforming growth factor β and activate renal fibrobalsts. 100,101,253 Hypoxia also activates fibroblasts directly to increase extracellular matrix deposition by increasing production of collagen and tissue inhibitor of metalloproteinase I and decreasing expression of collagenase. 266 This activation of fibroblasts, along with the recruitment of inflammatory cells and the damage done to tubular epithelial cells, all lead to tubulointerstitial fibrosis.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…Under these circumstances urinary protein excretion, inflammatory cell infiltration into the kidney, and renal epithelial-to-mesenchymal transition were all increased. 100,101 Consequently, there appears to be a direct link between hypoxia and the progression of CKD.…”
mentioning
confidence: 99%